THE INFLUENCES OF COMMUNICATION AND WORK MOTIVATION OF THE GOVERNMENT OFFICIALS ON THE QUALITY OF LAND CERTIFICATION SERVICE AT THE SERVICE AT THE AGRARIA MUNICIPALITY OF SOUTH JAKARTA - Sunarto, Sunarto (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
Thzs research   deals  with  the poor  quality  of land certification  service  and poor communication    and  working  motivation   of government   employees  at the  Land Office   of   South   Jakarta    Municipality.     This  research    design   in  form    of explanatory   survey  using  line  statistics   analysis  completed   111i1h   confirmation using qualitative   data  through  participatory   observation  on documents  and  in- depth  interviews   lo find   out the essence  of what and how good  communication and working  motivation  of employees  in handling  certificate  applicants  are.  The result  of  the  research  shows   that  quality   of communicators    was the poorest, whereas  the disturbance  dimension  was found  the best. Working  motivation  and accountability   1vere other  dimensions found   the poorest  compared  lo other five